Gestão do conhecimento na educação ambiental: estudo de casos em programas de educação ambiental em universidades brasileiras - Escrivão, Giovana [UNESP]; Nagano, Marcelo (Escola de Ciência da Informação da UFMG, 2014)
Although the importance of knowledge management for any organizational environment as a strategy to confront the current instability has been widely recognized, little is known concerning the creation of organizational knowledge. Different contexts that knowledge management can be applied providing creation of new knowledge and its better use, like in the environmental education on accounting of growing environmental degradation. The present paper analyzes and describes the process of knowledge creation in environmental education programs at the two largest Brazilians public universities by conducting comparative case studies. This research can be classified as qualitative with a descriptive characteristic conducted through case studies, as a detailed study of the characteristics of the environmental education programs was realized in two major Brazilian universities. The methods used to collect and analyze the data were interviews and content analysis. At the end of the study it was made some suggestions of practices that can provide manage of the environmental knowledge and incentive for the creation of new knowledge to environmental education programs, as replacing the teams, that are homogeneous, by heterogeneous teams in order to share different contexts, know-how and knowledge. Concerning theory of knowledge creation, some results of studied cases made available the identification of eight observations that question some assumptions of this theory, as the high turnover or the guaranteed stability on work can perform on employees' commitment to knowledge creation.

A importância da gestão do conhecimento para qualquer ambiente organizacional como uma estratégia de enfrentamento à instabilidade atual é amplamente reconhecida, apesar disso, pouco se sabe sobre a criação do conhecimento organizacional. Diversos são os contextos em que a gestão do conhecimento pode ser aplicada proporcionando a geração de novos conhecimentos, sendo um deles a educação ambiental, diante da crescente degradação ambiental. O objetivo dessa pesquisa é analisar e descrever o processo de criação do conhecimento em programas de educação ambiental. A pesquisa tem natureza qualitativa e caráter descritivo e pode ser definida como estudo de casos, pois foi realizado um estudo aprofundado das características dos programas de educação ambiental em duas das principais universidades brasileiras. Os métodos utilizados para coletar e analisar os dados foram a entrevista e a análise de conteúdo. Ao final da pesquisa pôde-se sugerir práticas aos programas de educação ambiental que podem proporcionar a gestão e estimular a criação de novos conhecimentos, como por exemplo, substituir as equipes, que são atualmente homogêneas, por equipes heterogêneas para que diferentes contextos, experiências e conhecimentos sejam compartilhados. No que diz respeito a teoria da criação de conhecimento, os casos estudados possibilitaram a identificação de observações sobre alguns pressupostas desta teoria, como por exemplo, a alta rotatividade dos alunos e a estabilidade garantida dos funcionários influem sobre o comprometimento destes com a criação de conhecimento.
Knowledge management in environmental education:case studies in environmental education programs in Brazilian universities
Keywords: Gestão do conhecimento; Criação do conhecimento; Conhecimento; Informação; Educação ambiental; Programas de educação ambiental; Universidades; Knowledge management; Knowledge creation; Knowledge; Information; Environmental education; Environmental education programs; Universities